The Effect of Plumbum and Cadmium on the Seeds Germination and Growth of C.Odorata, T. paniculatum and C. pallida - Koh, Chun Hou (2017)
Heavy metals pollution has been a concern and is getting worse each day which could bring adverse effects toward organisms such as plants and animals. Plants will uptake the heavy metals that are present in the surrounding environment and either die due to intolerance or accumulate in edible parts which will cause heavy metals poisoning to organisms that consume the plants such as humans. This study is carried out to determine the effect of heavy metals such as lead (Pb) and Cadmium (Cd) on the germination of various seeds of Chromolaena odorata, Talinum paniculatum and Crotalaria pallida and the growth of shoot and root at day 14. The seeds were grown in the Petri dish with cotton and treated with different concentrations (0, 1, 5, 10, 50, 100, 200, 400, 600, 800, 1000 mg/L) of lead (Pb) and (0, 0.1, 0.5, 1, 5, 10, 50, 100, 150, 200, 300 mg/L) cadmium (Cd) solution. The germination percentage and the length of the shoot and root were being observed and measured for a duration of 14 days. The increasing Pb and Cd concentrations resulted in the reduction in the germination percentage, length of shot and root. C. odorata had the highest germination percentage of 42.31% when compared to both different concentrations of Pb and Cd. The highest germination percentage of 33.85% was obtained when T. paniculatum was grown in Pb at 0 mg/L whereas the highest germination percentage of 35.38% was obtained at 50 mg/L of Cd. For C. pallida, the highest germination percentages of 55.38% at 1 mg/L of Pb and 45.38% at 0 mg/L of Cd were obtained. When the seeds were grown on cotton containing Pb, C. odorata had the highest length of shoot and root of 2.2 cm and 1.4 cm respectively at 0 mg/L; T. paniculatum had the highest length of shoot and root of 2.3 cm at 1 mg/L and 1 cm at 5 mg/L respectively whereas C. pallida had the highest length of shoot and root of 5.2 cm at 0mg/L and 2.3 cm at 10 mg/L respectively. Moreover, when the seeds were grown in Cd condition, C. odorata had the highest length of shoot of 2.2 cm and root of 1.5 cm at 0 mg/L; T. paniculatum had the highest length of shoot of 1.3 cm at 0 mg/L and root of 1.3 cm at 0.1 mg/L whereas C. pallida had the highest length of shoot of 5.2 cm at 0 mg/L and root of 1.7 cm at 0.5 mg/L. In conclusion, C. pallida displayed high overall germination percentage, length of shoot and root when exposed to Pb and Cd as compared to other plant species tested. Hence, C. pallida might serve as a suitable plant that could be used to remediate Pb and Cd contaminated area.